“Adventures in science”: casting scientifically talented youth as national resources on American radio, 1942-1958. - Terzian, SevanG. (Paedagogica Historica, 2008)
From 1942 to 1958, a national weekly programme on CBS radio and presented by Science Service, Inc. devoted 37 of its broadcasts to profiling American high school students' achievements in science talent searches, clubs and fairs. These “Adventures in Science” radio programmes cast scientifically talented youth as potential contributors to national goals in the hopes of eliciting greater public appreciation of science and science education. This characterisation reflected meritocratic and democratic justifications for American science education. First, the host of this series and director of Science Service, Watson Davis, argued that these students could someday become elite scientists to help compensate for the perceived scientific manpower shortages during World War Two and the postwar era. As a result, listeners of these programmes should value these talented boys and girls, because the potential military applications of their research could safeguard the nation from external threats. Second, journalistic intermediaries such as Davis and announcers at local broadcast sites presented the importance of students' scientific work in practical terms: as commercial and domestic products to be evaluated and consumed by democratic citizens. Listeners should therefore appreciate the contributions of science and science education to their everyday lives, material comforts and a vibrant consumer economy - especially in the postwar era. This article concludes that these popular radio programmes demonstrate that the enlistment of science education for national political and economic agendas both during and after the Second World War well preceded the US government's curricular response to the launching of Sputnik with the National Defense Education Act of 1958.